Goods Sorting Tool Based on Weight of Goods Using Arduino Nano - Ihwan, Robi Irlanda; Candra, Oriza (Jurnal Teknik Elektro Indonesia, 2024)
The use of conveyors with scales in industry as part of the quality control process has become an important requirement that increasingly dominates the manufacturing sector. Consistent product quality and accurate monitoring of weight or other parameters during production have become essential to meet stringent quality standards and customer expectations. Hence, many industries have prioritized investment in the manufacture of weighing conveyor. Scale-equipped conveyors enable continuous, real-time monitoring of product quality. Scales integrated on the conveyor enable quick identification of defective products or products that do not conform to standards. This helps in reducing the risk of defective products reaching the market and helps companies meet applicable industry standards. In addition, the use of conveyors with scales also improves production efficiency by avoiding error-prone manual work, thus supporting production cost control. This research uses a weight sensor that can double as a product count counter at each weight count set point. The weight set points are limited to 3 different types of product weight. After testing and analyzing the test results, it can be concluded that the tool can function properly which can classify 8 products per minute with 100% accuracy.